2011
DOI: 10.1371/journal.pone.0028367
|View full text |Cite
|
Sign up to set email alerts
|

Cyclical and Patch-Like GDNF Distribution along the Basal Surface of Sertoli Cells in Mouse and Hamster Testes

Abstract: Background and AimsIn mammalian spermatogenesis, glial cell line-derived neurotrophic factor (GDNF) is one of the major Sertoli cell-derived factors which regulates the maintenance of undifferentiated spermatogonia including spermatogonial stem cells (SSCs) through GDNF family receptor α1 (GFRα1). It remains unclear as to when, where and how GDNF molecules are produced and exposed to the GFRα1-positive spermatogonia in vivo.Methodology and Principal FindingsHere we show the cyclical and patch-like distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 52 publications
3
45
1
Order By: Relevance
“…1C; Supplementary Figure S6, see section on supplementary data given at the end of this article). Anti-GFRa1 and anti-HuB immunostaining revealed that the GFRa1C undifferentiated spermatogonia (including spermatogenic stem cells; Sato et al 2011) and HuBC differentiated spermatogonia (including pre-leptotene spermatocytes; Supplementary Figure S7) are detectable in the basal compartment of the seminiferous tubules on day 4 after DT treatment. However, both spermatogonial populations were depleted by day 10 after DT treatment (Fig.…”
Section: Dt Injection Induces Sertoli Cell Degeneration In Postnatal mentioning
confidence: 99%
“…1C; Supplementary Figure S6, see section on supplementary data given at the end of this article). Anti-GFRa1 and anti-HuB immunostaining revealed that the GFRa1C undifferentiated spermatogonia (including spermatogenic stem cells; Sato et al 2011) and HuBC differentiated spermatogonia (including pre-leptotene spermatocytes; Supplementary Figure S7) are detectable in the basal compartment of the seminiferous tubules on day 4 after DT treatment. However, both spermatogonial populations were depleted by day 10 after DT treatment (Fig.…”
Section: Dt Injection Induces Sertoli Cell Degeneration In Postnatal mentioning
confidence: 99%
“…5 The microenvironment of SSCs in the basal compartment of the seminiferous epithelium is important for the maintenance and self-renewal of these cells 6,7 because Sertoli cells provide the growth factors necessary for selfrenewal in this microenvironment. [8][9][10][11] Glial cell line-derived neurotrophic factor (GDNF) is the most crucial factor in the balance between self-renewal and differentiation in the SSC pool [12][13][14] as well as the promotion of SSCs' self-renewal. Without this factor, either spermatogonial aggregates do not develop or SSCs perish.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps, a recommended way to reach these goals is culture of stem cells in the presence of growth factors. Among the growth factors, GDNF (Glial-Cell-Line-Derived Neurotrophic Factor) is the most crucial factor to promote SSC self-renewal leading to a balance set between SSCs self-renewal and differentiation [47][48][49]. Without GDNF, spermatogonial aggregation cannot occur or SSCs may be perished [50].…”
Section: Discussionmentioning
confidence: 99%